Non-serogroupable Neisseria meningitidis pneumonia in an immunocompetent patient with severe COVID-19 pneumonia: A case report - Hiroki Kojima; Fukumi Nakamura-Uchiyama; Tsukasa Ariyoshi; Atsushi Kosaka; Takuya Washino; Naoya Sakamoto; Sentaro Iwabuchi; Jun Makino (IDCases, 2023)
Background: Non-serogroupable Neisseria meningitidis (N. meningitidis), the most common type of N. meningitidis in asymptomatic carriers, rarely causes infections. Most reported cases of infection are in patients with immunodeficiency, primarily complement deficiencies. Case presentation: A 54-year-old immunocompetent man was transferred to our hospital to treat severe coronavirus disease 2019 (COVID-19). The patient presented with cough producing a large amount of purulent sputum, which was considered an atypical presentation of COVID-19. Gram staining of the sputum revealed a large number of gram-negative diplococci phagocytosed by many neutrophils, and a diagnosis of bacterial pneumonia was established. The culture yielded non-serogroupable N. meningitidis, and the patient was diagnosed with non-serogroupable N. meningitidis pneumonia. Potential immunodeficiency was considered; however, testing including human immunodeficiency virus and complement factors showed no abnormalities. Conclusions: We report herein a rare case of non-serogroupable N. meningitidis pneumonia that occurred in an immunocompetent patient during the course of severe COVID-19. We consider impaired T cell function attributable to COVID-19 and dexamethasone administration may have triggered a transient immunosuppressive state and led to non-serogroupable N. meningitidis pneumonia.